Effects of cypionate and estradiol benzoate in cross breed heifers on pregnancy rate - Vera Alava, Hjalmar (2021)
The objective of this research was to determine the effect of Estradiol Cypionate (ECP), at the time of withdrawal of the Progesterone vaginal device or Estradiol Benzoate (EB), 24 hours later on the pregnancy rate in heifers inseminated at fixed time (FTAI). Seventy-two Bos indicus x Bos taurus crossbred heifers of body condition 3.0 to 3.5 (Scale 1 to 5), body weight between 300 to 400 kg were selected. The animals were divided into three groups A, B and C. All animals were synchronized to estrus using EB + Progesterone (DIB 0.5) + Prostaglandin F2-Alpha. Ovulation was induced by administering 0.5 and 1 milligram estradiol cypionate to groups A and B on day zero when the progesterone vaginal device was removed. To group C, 1 milligram of Estradiol Benzoate was administered 24 hours after the end of progesterone treatment. The administration of ECP at a dose of 0.5 milligram, showed the best uniformity in the manifestation of estrus, higher percentage of conception 68.1% and pregnancy 62.5% than the rest of the treated groups, with respect to body weight did not influence pregnancy. It is concluded that the administration of low dose ECP at zero hours after the end of the progesterone treatment showed better indicators on pregnancy percentages as well as allowing a one-day reduction in field work with adequate pregnancy rates. However, the range of 300 to 400 kg of body weight at the beginning of treatment had no effect on fertility in Bos indicus x Bos taurus crossbred heifers.